1975
DOI: 10.1152/jappl.1975.38.6.1030
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation during marathon running in cool, moderate, and hot environments

Abstract: A well-trained subject, age 38, ran continously for periods ranging from 60 to 165 min on a motor-driven treadmill at 255.7 m/min while confronted with an airflow equivalent to running speed in cool, moderate, and hot environments. After a period of intensive heat acclimatization, treadmill runs were repeated in the moderate and hot conditions. Measurements were also obtained outdoors in a competitive marathon race. Sweat rate (SR) and mean skin temperature (Ts) were linearly related to Tdb. Acclimatization di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(53 citation statements)
references
References 0 publications
0
50
0
3
Order By: Relevance
“…Physiological adaptations take, depending on the parameters, as little as three or as much as 14 days of continuous exposure to heat-stress (Armstrong 2000). Fatigue during prolonged exercise occurs earlier at higher environmental temperatures (Saltin et al 1972) but can be delayed after a process of HA (Adams et al 1975;Nielsen et al 1993). It has been suggested that when a person exercises in the heat, the drive to exercise is diminished by increased core temperature (Bruck and Olschewski 1987;Fink et al 1975;Nielsen et al 1990) and that the reduced body temperature after HA results in a prolonged exercise time to exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological adaptations take, depending on the parameters, as little as three or as much as 14 days of continuous exposure to heat-stress (Armstrong 2000). Fatigue during prolonged exercise occurs earlier at higher environmental temperatures (Saltin et al 1972) but can be delayed after a process of HA (Adams et al 1975;Nielsen et al 1993). It has been suggested that when a person exercises in the heat, the drive to exercise is diminished by increased core temperature (Bruck and Olschewski 1987;Fink et al 1975;Nielsen et al 1990) and that the reduced body temperature after HA results in a prolonged exercise time to exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of sodium in sweat varies widely but is usually 15 to 65 mEq/L, with highly fit athletes generally excreting sweat with sodium concentrations Ͻ40 mEq/L (38,76). The volume of sweat during exercise also varies widely, from approximately 250 ml/h to Ͼ2 L/h, again being less in more fit athletes (77,78). This loss of a substantial amount of hypotonic fluid may seem to protect against the development of hyponatremia.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The detrimental eects of high environmental temperatures on the performance of prolonged, submaximal exercise have been well established for men (Adams et al 1975;Galloway and Maughan 1997;Suzuki 1980), but, there is a dearth of information about women. In addition, it has been shown that many sports (among them ®eld hockey, rugby and soccer) require men and women to exercise maximally for short periods, lasting perhaps a few seconds, interspersed with longer spells of rest or lower intensity activity (Williams 1990).…”
Section: Introductionmentioning
confidence: 99%